Aftiphilin Regulation of Myosin Light Chain Kinase Activity Promotes Actin Dynamics and Intestinal Epithelial Barrier Function - Law, Ivy Ka Man; Fang, Kai; Pothoulakis, Charalabos; Rankin, Carl Robert (Frontiers in Gastroenterology, 2022)
The expression levels of aftiphilin (AFTPH) are significantly lower in inflamed colonic tissues from patients with ulcerative colitis (UC) and mice with experimental colitis. During colonic inflammation, the selective permeability of the colonic epithelium is compromised largely due to dysregulation of proteins associated with either the tight junction (TJ) complex and actomyosin contraction rings. Here, we hypothesized that inflammation-associated reduction in AFTPH levels might cause an increase in the selective permeability of the colonic epithelium. In this study, we measured the transepithelial electric resistance (TEER), sodium (Na+) ion flux and dextran permeability in polarized colonic epithelial cells after manipulation of AFTPH. Silencing of AFTPH reduced TEER, increased Na+ ion flow and dextran permeability. Examination of mRNA and protein levels of multiple TJ proteins and Na+ ion transporters suggested that AFTPH deficiency did not significantly change expression of most of these transmembrane proteins. While the gross structure of the TJs in AFTPH gene-silenced cells appeared normal, elevated levels of junctional Occludin were observed. Most notably we observed that AFTPH co-localized with myosin light chain kinase (MLCK) and attenuated cellular MLCK activity as observed by phospho- myosin light chain 2 (pMLC2) western blots. Importantly, inhibition of MLCK activity reversed the reduction of TEER in AFTPH-deficient monolayers. Lastly, examination of microvilli by transmission electron microscopy and immunofluorescence imaging of actin filament arrangement demonstrated that AFTPH deficiency also affected filament arrangement in colonic epithelial cells. Taken together, these results suggest that AFTPH regulates intestinal epithelial permeability and actin polymerization in colonic epithelium through interfering with MLCK/MLC interactions.